Sharing science, building bridges, and enhancing impact: Public-Private Partnerships in the CGIAR - Spielman, David J.; Hartwich, Frank; von Grebmer, Klaus; Syngenta Foundation for Sustainable Development; U.K. Department for International Development (International Food Policy Research Institute, 2007)
This study, which examines the role of public–private partnerships in international agricultural research, is intended to provide policymakers, research managers, and business decisionmakers with an understanding of how such partnerships operate and how they potentially contribute to food security and poverty reduction in developing countries. The study examines public–private partnerships in light of persistent market failure, institutional constraints, and systemic weaknesses, which impede the exchange of potentially pro-poor knowledge and technology. The study focuses on three key issues: whether public–private partnerships contribute to reducing the cost of research, whether they add value to research by facilitating innovation, and whether they enhance the impact of research on smallholders and other marginalized groups in developing-country agriculture. The study examines 75 projects undertaken by the research centers and programs of the Consultative Group on International Agricultural Research (CGIAR) in partnership with various types of private firms. Data and information were obtained through document analysis, semi-structured interviews with key informants, and an email survey of CGIAR centers. The resulting analysis provides a characterization of public–private partnerships in the CGIAR and describes the factors that contribute to their success. These finding are important to improving both public policy and organizational practices in the international agricultural research system.